PRIORITIZING TASKS IN INFORMATION SYSTEM PROJECTS: A NOVEL APPROACH USING VIKOR METHOD - Soetam Rizky Wicaksono (Department of Computer Engineering, Universitas Wiralodra, 2023)
Information Systems (IS) projects often face significant challenges, with many failing to meet their objectives. One of the key factors contributing to these failures is the improper prioritization of tasks. This article addresses this issue by proposing a comprehensive approach to task prioritization in IS projects using the VIKOR method. The approach takes into account four key criteria - cost, time, risk, and complexity - and uses the VIKOR method to rank tasks based on these criteria. The VIKOR method provides a systematic and objective way of prioritizing tasks, ensuring effective resource allocation, appropriate risk management, and the achievement of strategic objectives. The application of the VIKOR method in the context of IS projects is a novel contribution of this article. However, it is also recognized that the proposed approach has its limitations and that further research is needed to consider additional criteria, explore other decision-making methods, and examine the dynamic nature of IS projects. Overall, this article contributes to the growing body of knowledge on project management in IS and provides a practical tool for project managers to improve their decision-making processes.